2018
DOI: 10.1186/s12934-018-0931-x
|View full text |Cite
|
Sign up to set email alerts
|

Bio-detheobromination of cocoa pod husks: reduction of ochratoxin A content without change in nutrient profile

Abstract: BackgroundUtilization of cocoa pod husks (CPH) in animal feed is hindered by the presence of theobromine, which is variably toxic to animals. Treatment of this agro-waste to remove theobromine, while preserving its nutrient content, would allow beneficial use of the millions of metric tonnes discarded annually. The aim of this study was to assess the suitability of selected theobromine-degrading filamentous fungi for use as bio-tools in degradation of theobromine in CPH.ResultsThe candidate fungi assessed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…There was a 46.97 to 77.2% decline in theobromine content of the cocoa pod husk meal postfermentation which is indicative of the ability of R. stolonifer to degrade the methylzanthine backbone of theobromine in the substrate. This reduction coefficient in theobromine agrees with the reports of Adamafio et al, (2011), Bentil et al, (2015), Amorim et al, (2017) and Oduro-Mensah et al, (2018) who recorded significant decline in theobromine concentration after microbial fermentation. A significant reduction in coefficient by 72% was reported for theobromine by Oduro-Mensah et al (2018) after employing a solid state fermentation of cocoa pod husk for 7 days using two strains of fungi, namely: Aspergillus niger and Talaromyces species which is still lower than 77% reported in this current study for the same fermentation period.…”
Section: Amino Acidsupporting
confidence: 92%
See 2 more Smart Citations
“…There was a 46.97 to 77.2% decline in theobromine content of the cocoa pod husk meal postfermentation which is indicative of the ability of R. stolonifer to degrade the methylzanthine backbone of theobromine in the substrate. This reduction coefficient in theobromine agrees with the reports of Adamafio et al, (2011), Bentil et al, (2015), Amorim et al, (2017) and Oduro-Mensah et al, (2018) who recorded significant decline in theobromine concentration after microbial fermentation. A significant reduction in coefficient by 72% was reported for theobromine by Oduro-Mensah et al (2018) after employing a solid state fermentation of cocoa pod husk for 7 days using two strains of fungi, namely: Aspergillus niger and Talaromyces species which is still lower than 77% reported in this current study for the same fermentation period.…”
Section: Amino Acidsupporting
confidence: 92%
“…This reduction coefficient in theobromine agrees with the reports of Adamafio et al, (2011), Bentil et al, (2015), Amorim et al, (2017) and Oduro-Mensah et al, (2018) who recorded significant decline in theobromine concentration after microbial fermentation. A significant reduction in coefficient by 72% was reported for theobromine by Oduro-Mensah et al (2018) after employing a solid state fermentation of cocoa pod husk for 7 days using two strains of fungi, namely: Aspergillus niger and Talaromyces species which is still lower than 77% reported in this current study for the same fermentation period. The degradation of theobromine by R. stolonifer could have been made possible by using theobromine as a sole carbon and energy source via the demethylase oxidase, xanthine dehydrogenase, xanthine oxidase, urease and uricase pathway (Yamaoka-Yano and Mazzafera, 1999;Dash and Gummade, 2006;Huq, 2006).…”
Section: Amino Acidsupporting
confidence: 92%
See 1 more Smart Citation
“…Among these strategies, physicochemical treatments have been proposed, such as the boiling of CBS [143,144] or hydrotropic extraction [144]. Also, several studies have proposed fungi fermentation treatments of CBS for bio-detheobromination, showing that species such as A. niger, Talaromyces, or P. ostreatus spawn are capable of metabolizing theobromine, obtaining up to a 78.13% theobromine content reduction in CBS [69,130,145,146].…”
Section: Utilization As Feedstuffsmentioning
confidence: 99%
“…Aroyeun and Adegoke [216] found an OTA reduction efficiency of 64.3%-95% by employing essential oils, while Manda et al [217] observed an average OTA decrease of 23.8% with just a controlled roasting process at 140 • C for 30 min. Oduro-Mensah et al [146] proposed a method employing filamentous fungi that degraded 31%-74% of the OTA contained in cocoa pods. Besides, CBS have been affirmed to be especially susceptible to fungi spoilage, due to the pulp residues that can remain on it after bean separation from the pods and fermentation, thus the occurrence of mycotoxins could also be partially prevented if special attention is directed to bean cleanliness after fermentation [218].…”
Section: Mycotoxinsmentioning
confidence: 99%